Diversity of Tylenchida nematodes in Coleoptera Coccinellidae in la Plata and Magdalena, Argentina. - Camino, Nora (2024)
This work was carried out between 2015 and 2020 in fields dedicated to intensive horticulture in the horticultural belts of La Plata and Magdalena. The objective was to determine species of pathogenic parasitic nematodes of vegetable pest insects. The samples were taken in summer squash (Curcubita máxima var. zapallito (Carr.) Millan, 1947), kale (Brassica oleracea L., 1753) and eggplant (Solanum melongena L., 1753), randomly selected sites.In these samplings the Coccinellidae Coleoptera of the genera Harmonia, Cycloneda and Epilachna were present. Six species of Tylenchida nematodes and one Mermithidae were found; species richness values were five for Harmonia axyridis (Pallas, 1773), and one for Cycloneda sanguinea (Linneaus, 1763) and Epilachna paenulata (Germar, 1824), respectively. The prevalence, intensity, abundance and dominance indices were higher for the nematodes Proparasitylenchus Wachek, 1955, Neoparasitylenchus Nickle, 1967 and Parasitylenchus Micoletzky, 1922, compared to Metaparasitylenchus (Wachek, 1955) Nickle, 1967, Sulphuretylenchus (Rühm, 1956) Nickle, 1967, Contortylenchus Rühm, 1956and the lowest value of the indices for the mermitid Hexamermis Steiner, 1924. The purpose of the work is to provide, for the first time for the region, a list of nematodes parasites of coccinellids.